2020
DOI: 10.3390/cancers12082148
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA and Mechanisms of Drug Resistance in Cancers of the Genitourinary System

Abstract: Available systemic treatment options for cancers of the genitourinary system have experienced great progress in the last decade. However, a large proportion of patients eventually develop resistance to treatment, resulting in disease progression and shorter overall survival. Biomarkers indicating the increasing resistance to cancer therapies are yet to enter clinical routine. Long non-coding RNAs (lncRNA) are non-protein coding RNA transcripts longer than 200 nucleotides that exert multiple types of regulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 207 publications
(269 reference statements)
0
23
0
Order By: Relevance
“…This feature suggests that these noncoding sequences may participate in the extremely complex process of life regulation. Among these noncoding sequences, long noncoding RNA (lncRNA) can regulate gene expression and protein activity by affecting chromatin modification and RNA splicing, thus occupying an important position [ 21 , 22 ]. The role of lncRNA in the occurrence, development, prognosis, and chemotherapy resistance of malignant tumours has become a research hotspot.…”
Section: Discussionmentioning
confidence: 99%
“…This feature suggests that these noncoding sequences may participate in the extremely complex process of life regulation. Among these noncoding sequences, long noncoding RNA (lncRNA) can regulate gene expression and protein activity by affecting chromatin modification and RNA splicing, thus occupying an important position [ 21 , 22 ]. The role of lncRNA in the occurrence, development, prognosis, and chemotherapy resistance of malignant tumours has become a research hotspot.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of testicular cancer, few lncRNAs have been linked to its pathogenesis ( 153 , 154 ), and even though no clinical studies are available for many of them, these lncRNA may represent promising drug targets or biomarkers.…”
Section: Discussion and Conclusive Remarksmentioning
confidence: 99%
“…Mechanistic investigations revealed that antisense lncRNAs can affect biological process in both the nucleus and cytoplasm, such as epigenetic modulations and translational control. Furthermore, the aberrant expression of antisense lncRNAs is responsible for chemoradioresistance, a major obstacle to cancer therapy [ 23 , 24 ]. Research on antisense lncRNAs has indicated their potential in therapeutic approaches; therefore, it necessary to summarize the roles and molecular mechanisms of antisense lncRNAs in the process of cancer development and progression.…”
Section: Antisense Lncrnas and Cancermentioning
confidence: 99%